Meta-Analysis of Direct and Indirect Effects of Father Absence on Menarcheal Timing - Guo, Shaolingyun; Lu, Hui Jing; Zhu, Nan; Chang, Lei (Frontiers in Psychology, 2020)
Despite extensive evidence of the association between father absence and early onset of menarche, whether father absence directly accelerates the onset of menarche or the association is mediated by other negative family psychosocial processes remains unclear. Reliable theories on the basis of which father absence has been investigated also vary. Within the life history (LH) theoretical framework, we conducted a meta-analysis of studies that investigated father absence, menarcheal timing, and various family disturbances that cause stress in children. We tested the hypothesis that father absence exerts a direct effect on menarcheal timing and an indirect effect on menarcheal timing mediated by integrated childhood stress. Quantitative synthesis using a two-stage meta-analytic structural equation modeling approach was applied to test our hypothesis. Based on 7 research articles (N = 4,619) that include at least one form of family stressor as well as father absence and menarcheal timing, integrated childhood stress emerged as a robust mediator of the association between father absence and early menarcheal timing, and the total effect of father absence on menarcheal timing had reduced in size after accounting for the mediating effect of childhood stress. The findings emphasize the importance of a father figure in regulating a child’s LH, including menarcheal timing.